2019
DOI: 10.1111/clr.13522
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic titanium surface‐induced macrophage modulation promotes pro‐osteogenic signalling

Abstract: Objectives As biomaterial‐induced modulation of mediators of the immune response may be a potential therapeutic approach to enhance wound healing events, the aim of this study was to delineate the effects of titanium surface modification on macrophage phenotype and function. Material and methods Rodent bone marrow‐derived macrophages were polarized into M1 and M2 phenotypes and cultured on micro‐rough (SLA) and hydrophilic modified SLA (modSLA) titanium discs. Macrophage phenotype and cytokine secretion were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
0
43
1
2
Order By: Relevance
“…To mediate a desirable transition from inflammation to healing, macrophage populations at an injury or implantation site shift from a pro‐inflammatory (M1) phenotype into an anti‐inflammatory (M2) phenotype. We and others have demonstrated that macrophage activation in response to biomaterial surface modifications in vitro is predictive of macrophage activation, inflammation resolution, and MSC recruitment in vivo (Donos et al., 2011; Hamlet et al., 2019; Hotchkiss et al., 2016; Hotchkiss et al., 2017; Hotchkiss et al., 2018; Wang et al, 2019a).…”
Section: Introductionmentioning
confidence: 92%
“…To mediate a desirable transition from inflammation to healing, macrophage populations at an injury or implantation site shift from a pro‐inflammatory (M1) phenotype into an anti‐inflammatory (M2) phenotype. We and others have demonstrated that macrophage activation in response to biomaterial surface modifications in vitro is predictive of macrophage activation, inflammation resolution, and MSC recruitment in vivo (Donos et al., 2011; Hamlet et al., 2019; Hotchkiss et al., 2016; Hotchkiss et al., 2017; Hotchkiss et al., 2018; Wang et al, 2019a).…”
Section: Introductionmentioning
confidence: 92%
“…No alternations in surface roughness and topography may lead to the effect that no significant differences in water contact angle of differently charged P (VDF-TrFE) surfaces. Therefore, the interference of the topography and wettability of biomaterials with the behavior of macrophages reported in numerous studies (Hotchkiss et al, 2016;Hamlet et al, 2019) were excluded in this work. Combining surface-potential results to analyze, the three P (VDF-TrFE) membranes with similar surface topography and wettability but different surface charge polarity, such as negatively (poled -), positively (poled +) and neutrally (nonpoled) charged P (VDF-TrFE) membranes, were fabricated in this study.…”
Section: Macrophage Adhesion and Morphology Affected By The Surface-charge Polarity Of P (Vdf-trfe) Membranesmentioning
confidence: 99%
“…On the other hand, Alfarsi et al [157] reported that surface hydrophilic modifications downregulated the gene expression profiles of several pro-inflammatory cytokines and of their associated proteins. Hamlet et al [158] investigated the comparative effect of two hydrophilic modified sandblasted/acid-etched (modSLA) and SLA Ti surfaces and the results showed a reduction in the gene expression profiles of the TNF-α, IL-1β, IL-1α cytokines and MCP-1 chemokine from the macrophages seeded on the surface of the hydrophilic Ti. In another study, Dai et al [159] evaluated the effect of hydrophilic Ti disks on RAW 264.7 murine macrophages and the results obtained revealed that the hydrophilic surface was able to upregulate the secretion of IL-10 and downregulate the secretion TNF-α, respectively.…”
Section: Surface Chemistry Alterationsmentioning
confidence: 99%
“…These observations suggested that microroughness could be beneficial for the healing and bone regeneration processes. However, Hamlet et al [ 158 ] reported contradictory results, demonstrating that Ti substrates with modified microroughness promoted an enhanced pro-inflammatory cytokine profile.…”
Section: Development Of Bone Biomaterials With Immunomodulatory Prmentioning
confidence: 99%